Experiências estéticas em instituições de reeducação de crianças e jovens - Müller, Andressa Coelho (2023)
This master's research, crossed by the philosophies of difference, proposes to focus on a re-education facility, as a space for social reintegration and readjustment, driven by the following question: what can aesthetic experiences do in a space for re-education of children and young people? The study carried out at the Institutional Shelter of an inland municipality in Rio Grande do Sul, Brazil; a space that welcomes children and adolescents from 0 to 18 years of age, at risk and/or whose rights have been violated, serving them without deprivation of liberty; proposes aesthetic experiences with children and teenagers who live in the institution with the aim of creating circumstances (Deligny, 2018a) amidst art and children and young people who live in re-education facilities. This is a research with art that is carried out in a network, which embraces Arts-Based Research (Oliveira; Charréu, 2016) as a methodological possibility, and is crossed by the continuous construction of visual and/or textual diaries (Oliveira, 2012). To this end, it calls upon authors such as Corazza (2009), Deligny (2015, 2018a, 2018b), Foucault (1988, 2014), Schérer (2009), Kastrup (2010, 2016), Kohan (2004, 2007, 2010, 2011) and Deleuze (1988-1989, 1992, 1999) to produce theoretical contagions and focus on a teaching that reinvents itself along the paths it takes. Finally, there is a focus on inventing new paces to inhabit re-education facilities. Paces open to the “useless”, in which there is no intention of producing or teaching anything to children at any age, assuming “infanciar” (Kohan; Fernandes, 2021) as a condition for the creation of circumstances.